ANALISA GEOTEKNIK PADA TANAH LUNAK PADA LONGSORAN TANGGUL SUNGAI TUNTANG - Su’udi Al Mukarom; Meilinda Dewi Astuti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Soil is a structure that chan be used as an embankment to prevent flooding in rivers and also sea eater tidal waves. Rivers are surface flows that are formed naturally or artificially and flow continuously to the sea. The condition of the soil on the river embankment is very unstable, which is directly adjacent to the irrigation canal, and the condition of the soil is very weak, causing the slope or embankment to collapse. The aim of this research is to determine soil stability analysis using the Plaxis Program Version 8.2, a geotechnical analysis program that can analyze soil stability using the finite element method which is capable of carrying out analyzes that can approximate actual behavior. Plaxis Version 8.2 provides various analyzes of displacement, stresses that occur in the soil, slope safety factors and others.The results of the analysis using the plaxis program Version 8.2 obtained maximum results. From the analysis of the Plaxis program on the construction of the Tuntang River Embankment landslide, it was found that in conditions where the soil was not repaired, it had a safety factor of 1.237 <1.5, which was smaller than the required safety factor, namely 1.5, so that the soil condition was unstable or a landslide. The condition of the soil in the channel was excavated and piled on top of the embankment, safety factor 1.105 < 1.5, this condition became worse due to the load on the embankment, the soil was strengthened by handling bamboo cerucuks to ensure that the soil did not experience movement at a distance of 0.5 m zig-zak. If a safety factor of 1.501 > 1.5, then with bamboo reinforcement the embankment can be overcome and not experience landslides.